RNA sequencing and lipidomics uncovers novel pathomechanisms in recessive X-linked ichthyosis - McGeoghan, Farrell; Camera, Emanuela; Maiellaro, Miriam; Menon, Manasi; Huang, Mei; Dewan, Priya; Ziaj, Stela; Caley, Matthew P.; Donaldson, Michael; Enright, Anton J.; O’Toole, Edel A. (Frontiers in Molecular Biosciences, 2023)
Recessive X-linked ichthyosis (RXLI), a genetic disorder caused by deletion or point mutations of the steroid sulfatase (STS) gene, is the second most common form of ichthyosis. It is a disorder of keratinocyte cholesterol sulfate retention and the mechanism of extracutaneous phenotypes such as corneal opacities and attention deficit hyperactivity disorder are poorly understood. To understand the pathomechanisms of RXLI, the transcriptome of differentiated primary keratinocytes with STS knockdown was sequenced. The results were validated in a stable knockdown model of STS, to confirm STS specificity, and in RXLI skin. The results show that there was significantly reduced expression of genes related to epidermal differentiation and lipid metabolism, including ceramide and sphingolipid synthesis. In addition, there was significant downregulation of aldehyde dehydrogenase family members and the oxytocin receptor which have been linked to corneal transparency and behavioural disorders respectively, both of which are extracutaneous phenotypes of RXLI. These data provide a greater understanding of the causative mechanisms of RXLI’s cutaneous phenotype, and show that the keratinocyte transcriptome and lipidomics can give novel insights into the phenotype of patients with RXLI.